The 2000 Presidential election and the foundations of party politics - Johnston, Richard (Cambridge University Press, 2004)
Campaigns suddenly seem to matter, as do questions about the electoral process in the aftermath of the 2000 presidential election. The authors examine the U.S. electoral process as an integrated event spanning a full year, drawing upon the Annenberg 2000 Election Study. The scale of their fieldwork is such that they have been able to isolate key turning points and that dynamics can be studied within certain segments. Johnston, Hagen and Jamieson have also utilized candidate appearances, news coverage, and campaign advertising to provide this integrated account of a U.S. campaign. Richard Johnston is Professor and Head of Political Science at the University of British Columbia and an Associate Member of Nuffield College, Oxford.